Bad apples or bad barrels? Qualitative study of negative experiences of encounters in healthcare. (June 2014) - Wessel, Maja; Lynöe, Niels; Juth, Niklas; Helgesson, Gert
Assessments of quality in healthcare often focus on treatment outcome or patient safety, but rarely acknowledge the importance of patients' encounters with healthcare personnel. The aim of this study was to gain an improved understanding of negative experiences of healthcare encounters by investigating experiences of the general population. A questionnaire was distributed to a randomly selected sample population of 1484 inhabitants in Stockholm County, Sweden. The material was subjected to conventional content analysis. Seventeen different types of complaint about negative encounters were identified, including unpleasant behavior, not being listened to, inadequate information, and discrimination. Two possible underlying explanations are discussed; structural factors relating to the organization and allocation of healthcare, and individual factors relating to the staff's attitudes and professional practice. The results indicate that different strands of actions are needed to reduce patients' negative experiences of encounters in healthcare, depending on the setting as well as on which of the two factors predominates.